Burger's Medicinal Chemistry and Drug Discovery 2003
DOI: 10.1002/0471266949.bmc093
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergics and Adrenergic‐Blocking Agents

Abstract: This chapter reviews the drugs currently available in the United States that exert their therapeutic effects through actions on α‐ and β‐adrenoceptors and biosynthesis, release, and processing of the neurotransmitter norepinephrine. Included in the review are drugs acting as selective and nonselective agonists and antagonists at both α‐ and β‐adrenoceptors, as well as drugs that interfere with norepinephrine biosynthesis and release. Therapeutic categories include antihypertensives, bronchodilators, antiglauco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Owing to the presence of ␤-ARs in various noncardiac tissues, beta-blockers have also been used to treat conditions like, migraine, essential tremor, situational anxiety, alcohol withdrawal, hyperparathyroidism, glaucoma, portal hypertension, and gastrointestinal bleeding (33). Most of the beta-blockers in clinical use currently are small molecules belonging to the aryloxypropanolamine class (34). Although they are widely used, physicians have encountered several problems associated with the currently available beta-blockers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the presence of ␤-ARs in various noncardiac tissues, beta-blockers have also been used to treat conditions like, migraine, essential tremor, situational anxiety, alcohol withdrawal, hyperparathyroidism, glaucoma, portal hypertension, and gastrointestinal bleeding (33). Most of the beta-blockers in clinical use currently are small molecules belonging to the aryloxypropanolamine class (34). Although they are widely used, physicians have encountered several problems associated with the currently available beta-blockers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a clinical trial using the D-enantiomer of the widely used beta-blocker sotalol, it was reported that the mortality increased by 65% compared to placebo (35). Many beta-blockers exhibit varying levels of lipophilicity and so have the ability to cross membrane barriers and reach the central nervous system, causing adverse effects like hallucinations and insomnia (34). Some beta-blockers are shown to increase insulin resistance and raise the risk of diabetes (36).…”
Section: Discussionmentioning
confidence: 99%
“…In many papers, compounds with isopropyl and tert-butyl group in the hydrophilic part of molecule are active beta-adrenolytics (Čižmáriková & Račanská, 1998;Bruchatá & Čižmáriková, 2010;Kečkéšová & Sedlárová, 2010). Lower beta-adrenolytic activity was observed in the compounds with other alkyl groups such as isobutyl and diethyl groups (Griffith, 2003). The large variety of different aromatic rings and substituents on nitrogen atom leads to compounds with combined pharmacological properties with affinity to both types of adrenergic receptor, α and β (Bruchatá & Čižmáriková, 2010).…”
mentioning
confidence: 99%
“…Pseudoephedrine (PSE) and phenylpropanolamine (PPA) are mixed‐acting sympathomimetic amines that have been used commonly as decongestants in the treatment of coughs and colds 10 – 14 . The effectiveness of PSE and PPA as decongestants is specifically related to the activation of α‐adrenergic receptors in the nasal mucosa, resulting in vasoconstriction, reduced blood flow, decreased mucosal edema, and, ultimately, improved nasal patency 15 , 16 . At mucosal sympathetic nerve endings, these agents directly stimulate adrenergic receptors (direct action) and displace norepinephrine from neuronal storage sites (indirect action).…”
mentioning
confidence: 99%
“…[10][11][12][13][14] The effectiveness of PSE and PPA as decongestants is specifically related to the activation of α-adrenergic receptors in the nasal mucosa, resulting in vasoconstriction, reduced blood flow, decreased mucosal edema, and, ultimately, improved nasal patency. 15,16 At mucosal sympathetic nerve endings, these agents directly stimulate adrenergic receptors (direct action) and displace norepinephrine from neuronal storage sites (indirect action). However, these same actions can also have a generalized effect on the peripheral cardiovascular system that can be exaggerated in the presence of an MAOI.…”
mentioning
confidence: 99%